E3 ubiquitin ligases: key regulators of osteogenesis and potential therapeutic targets for bone disorders - Zhang, Heng-Rui; Wang, Yang-Hao; Xiao, Zhen-Ping; Yang, Guang; Xu, Yun-Rong; Huang, Zai-Tian; Wang, Wei-Zhou; He, Fei (Frontiers in Cell and Developmental Biology, 2024)
Ubiquitination is a crucial post-translational modification of proteins that mediates the degradation or functional regulation of specific proteins. This process participates in various biological processes such as cell growth, development, and signal transduction. E3 ubiquitin ligases play both positive and negative regulatory roles in osteogenesis and differentiation by ubiquitination-mediated degradation or stabilization of transcription factors, signaling molecules, and cytoskeletal proteins. These activities affect the proliferation, differentiation, survival, and bone formation of osteoblasts (OBs). In recent years, advances in genomics, transcriptomics, and proteomics have led to a deeper understanding of the classification, function, and mechanisms of action of E3 ubiquitin ligases. This understanding provides new insights and approaches for revealing the molecular regulatory mechanisms of bone formation and identifying therapeutic targets for bone metabolic diseases. This review discusses the research progress and significance of the positive and negative regulatory roles and mechanisms of E3 ubiquitin ligases in the process of osteogenic differentiation. Additionally, the review highlights the role of E3 ubiquitin ligases in bone-related diseases. A thorough understanding of the role and mechanisms of E3 ubiquitin ligases in osteogenic differentiation could provide promising therapeutic targets for bone tissue engineering based on stem cells.